Communication patterns in Javanese families to build family resilience in the digital era - Wijayanti, Agustina Tri; Dwiningrum, Siti Irene Astuti; Saliman, Saliman (Informasi, 2024)
This study aims to find communication patterns in Javanese families to build family resilience in the digital era. This study used qualitative research methods of phenomenological studies. The subjects in the study were determined through purposive sampling, namely 5 families in Yogyakarta, Indonesia. The collection of research data uses in-depth interviews and observations, while data analysis is through Interpretative Phenomenological Analysis. The results of this study are as follows: Communication patterns for Javanese families in the digital era through a) parents as role models through setting examples in increasing spirituality and positive habituation, parents need to have responsive Digital skills. Family resilience patterns in childcare in the digital era need to be built by: a) building humanist dialogue, respecting each other, listening and responding to each other, making comfortable not depressed and afraid in the process then this is a process that can be developed in families in the digital age. b) democratic-contextual, in facing challenges and crises in the family, parents also need to develop a democratic parenting style that suits the needs of each child.